#### Answer

Input: -1
Output: $\frac{12}{5}$

#### Work Step by Step

We substitute x = -1 into the function.
$-\frac{12(-1)}{5}=-\frac{-12}{5}=\frac{12}{5}$

Published by
Prentice Hall

ISBN 10:
0133186024

ISBN 13:
978-0-13318-602-4

Input: -1
Output: $\frac{12}{5}$

We substitute x = -1 into the function.
$-\frac{12(-1)}{5}=-\frac{-12}{5}=\frac{12}{5}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.